YuYu Hakusho, Vol. 1 : :Goodbye, material world! - Togashi, Yoshihiro (Shonen Jump graphic novel, 2003)
Fourteen-year-old Yusuke Urameshi is trying to prove himself worthy of returning to life, and along the way, he and his spirit guide Boton have to deal with evil curses, bullies, and the ghost of a little girl.